Detecção sorológica para Leptospira spp. em cães domiciliados e de abrigo procedentes do município de Arapiraca, Alagoas, Brasil. - Pinto, Gabriela de Lima Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Leptospirosis is a neglected zoonosis with a wide global distribution, with domestic dogs acting as an important link in the transmission chain. Considering the importance of this zoonosis within the One Health context, the present study aimed to conduct a serological survey using the Microscopic Agglutination Test (MAT) in 300 dogs from Arapiraca (AL), including 150 shelter dogs and 150 owned dogs, correlating the results with possible risk factors. Serological results revealed a seroprevalence of 60/300 (20%), with 28/300 (9.3%) reactive shelter dogs and 32/300 (10.7%) owned dogs, and a slight predominance of seroprevalence in females, with 36/300 (12%), compared to males, with 24/300 (8%). Among the 28 reactive shelter dogs, 14 (23.33%) presented antibodies to serovar Canicola, 3 (5%) to Tarassovi, and 1 (1.67%) to Pomona. Among the 32 owned dogs, 11 (18.33%) were seroreactive to Canicola, 1 (1.67%) to Tarassovi, and 6 (10%) to Pomona. In the sample studied, the slight predominance of reactivity observed according to origin and sex indicated no association with risk factors for seroprevalence; however, the results demonstrated that seroreactive dogs may still pose a risk to contacts by presenting antibodies against potentially pathogenic serovars.
Serological detection of Leptospira spp. in domestic and shelter dogs from the municipality of Arapiraca, Alagoas, Brazil.
Keywords: Diagnóstico; Leptospirose; Cães; Zoonoses; Fatores de risco